Political Transtactions and Expenxive Costs on Regional Head Election - Arianto, Arianto (Journal of Local Government Issues, 2018)
Once the proliferation of regional head elections in Indonesia recently shows that our society many are interested to become a head of the region because there is recognition of its existence within the community so that competing both from the bureaucrats and from the private or legislative.The political costs incurred are not written so it is very difficult to identify how much each party pegs the price is not the same depending on the number of seats in the legislature or the amount of support available in the region or the networks that belong to the village will be different from the new party. Likewise, if through an independent channel, so much money must be spent to get administrative support from the community as from certain groups or individual, not to mention the cost of campaigns that must be issued by the candidate pair, almost not comparable if calculated by the salary of a regional head with the cost incurred, but it is still many who are interested to become a governor or mayor.Various studies conducted by many experts show, even though democracy is something that deserves to have aspired, it turns out that democracy produces many problems, even new problems that would not exist if not practiced democracy. Legislation has not regulated and limited the expenditures of candidates before and after the campaign, how much money is spent before and after the campaign, so it cannot be supervised. Supervision conducted by Banwaslu, PPATK and law enforcement officers is still not effective because there are still many gaps that can be done by a regional head in different ways and tactics.Key Words: Money Politics, Democracy, Political Monitoring.